Conceptualization, use, and outcomes associated with compassion in the care of youth with childhood-onset disabilities: a scoping review - Patsakos, Eleni M.; Patel, Stuti; Simpson, Robert; Nelson, Michelle L. A.; Penner, Melanie; Perrier, Laure; Bayley, Mark T.; Munce, Sarah E. P. (Frontiers in Psychology, 2024)
To examine the scope of existing literature on the conceptualization, use, and outcomes associated with compassion in the care of youth with childhood-onset disabilities.: A protocol was developed based on the Joanna Briggs Institute (JBI) scoping review method. MEDLINE, EMBASE, PsycINFO, Cochrane Central Register of Controlled Trials, and EBSCOhost CINAHL, were searched.Results: Eight studies were selected for inclusion; four used quantitative methodology, and four used qualitative methods. Compassion was not defined a priori or a posteriori in any of the included studies. The concept of self-compassion was explicitly defined only for parents of youth with childhood-onset disabilities in three studies a priori. The most reported outcome measure was self-compassion in parents of youth with childhood-onset disabilities. Self-compassion among parents was associated with greater quality of life (QoL) and resiliency and lower stress, depression, shame and guilt.Discussion: There is limited evidence on the conceptualization, use, and outcomes associated with compassion among youth with childhood-onset disabilities. Self-compassion may be an effective internal coping process among parents of youth with childhood-onset disabilities. Further research is required to understand the meaning of compassion to youth with childhood-onset disabilities, their parents and caregivers.'What this paper adds' § The conceptualization of compassion or self-compassion among youth with childhoodonset disabilities was not discussed. § Compassion was not defined a priori or a posteriori in any of the included studies.COMPASSION IN YOUTH WITH CHILDHOOD-ONSET DISABILITIES 2 § Self-compassion was conceptualized by established definitions only for parents of youth with childhood-onset disabilities. § Several studies liberally used the terms 'compassion' and 'compassionate care'. § The Mindfulness-Based Positive Behavior Support program was significantly better at enhancing compassion satisfaction and reducing caregiver-perceived psychological stress.